Targeting OAS3 for reversing M2d infiltration and restoring anti-tumor immunity in pancreatic cancer - Shaopeng Zhang; Ximo Xu; Kundong Zhang; Changzheng Lei; Yitian Xu; Pengshan Zhang; Yuan Zhang; Haitao Gu; Chen Huang; Zhengjun Qiu (Cancer Immunology, Immunotherapy)
Abstract Abundant infiltration of tumor-associated macrophages (TAMs) within the tumor stroma plays a pivotal role in inducing immune escape in pancreatic cancer (PC). Lactate serves as a direct regulator of macrophage polarization and functions, although the precise regulation mechanism remains inadequately understood. Our study revealed that PC cells (PCs) promote macrophage polarization toward M2d through high lactate secretion. M2d is characterized by elevated secretion of IL-10 and VEGF-A, which diminish CD8+T cells cytotoxicity and promote tumor neoangiogenesis simultaneously. Additionally, we identify 2,5’-oligoadenylate synthase 3 (OAS3) as an essential regulator of M2d polarization, upregulated by PCs via lactate/METTL3/OAS3 axis. Increased OAS3 expression in TAMs correlates with m6A modification mediated by METTL3 on OAS3 mRNA and is associated with poorer prognosis in PC patients. OAS3 deficiency in macrophages substantially impairs IL-10highVEGF-AhighM2d polarization and their pro-tumor functions while enhancing the therapeutic efficacy of gemcitabine and anti-PD-L1 mAb in humanized mouse models. In conclusion, OAS3 presents as a promising immune therapeutic target for reversing IL-10highVEGF-AhighM2d infiltration and restoring CD8+T cell-mediated anti-tumor immunity in pancreatic cancer. Graphical abstract